Sprouting of chayote (Sechium edule (Jacq.) Sw.) as influenced by various postharvest treatments - Bayogan, Emma Ruth V. (Banwa, 2019)
Chayote, a gourd which has good nutrional properties, is one of the vegetable crops in the Philippines with inadequate information on its inhibition or promotion of sprouting upon application of postharvest treatments.